Exclusion, marginalization and peripheralization. Conceptual concerns in the study of urban inequalities. - Bernt, Matthias; Colini, Laura (My University, 2013)
The main literature addressing exclusion and marginalization and extracted main propositions and developments was critically reviewd. We summarize these and discuss implications for our research on urban disparities in German cities. To guide our analysis, we have organised our argument around four key questions: a) Which conceptual and political backgrounds have the concepts of exclusion and marginality emerged from? b) How are the concepts defined and how are they applied in empirical research? c) Which critiques and modifications regarding these concepts can be identified? d) Which are the main insights a study on the making of urban peripheries can gain from the concepts of exclusion and marginalization? The answers to these questions are organised in three sections. It starts with the view of the concepts "exclusion" in the first and move on to the concept of "marginality" in the second section. The third section summarizes main concepts in the discussion on exclusion and marginality and discusses the implications of these debates for the research project "Urban Policies and Peripheralization".
Keywords: Stadtforschung; Stadtsoziologie; Bevölkerungsstruktur; Strukturwandel; Problemraum; Segregation; Stadtquartier; Peripherie; Peripherraum; Strukturschwäche; Deindustrialisierung; Sozialraum; Polarisierung; Exklusion; Regionale Disparität; Literaturstudie